Pendampingan dalam pengembangan media pembelajaran sebagai salah satu upaya untuk memperoleh sertifikasi bagi guru-guru SMK 1 Watampone - Dian Riani Said; Andi Trisnowali ms; Andi Srimularahmah; Aisyah Nursyam (Pendidikan Matematika, FKIP Universitas Mataram, 2021)
Community Service Activities in the form of assistance in the development of learning media aim to provide knowledge and skills in developing learning media that meet the requirements for certification for teachers. The ability to develop instructional media is expected to accelerate and facilitate the acquisition of in-service teacher certification. The target audience in this PPM activity is the 26 teacher of SMK 1 Watampone. Assistance in the development of instructional media is carried out by means of lectures, demonstration and exercises accompanied by question and answers. The Lecture method is used to explain the introductory concepts of professional teachers and teacher certification and the theory of instructional media. The demonstration method is used to show a work process, namely the stages of developing computer-based learning media, while the training method is to practice making media that meets the requirements of the teacher certification program. While the question and answer method is to give participants the opportunity to consult in overcoming obstacles in the development of learning media. The benefits that participants can get from activities include being able to compile and develop computer-based learning media according to the training subject being taught.